Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a.\)
\(\left(x^2-25\right):\dfrac{2x+10}{3x-7}\)
\(=\left(x-5\right)\left(x+5\right).\dfrac{3x-7}{2\left(x+5\right)}\)
\(=\dfrac{\left(x-5\right)\left(x+5\right)\left(3x-7\right)}{2\left(x+5\right)}\)
\(=\dfrac{\left(x-5\right)\left(3x-7\right)}{2}\)
\(b.\)
\(\dfrac{x^2+x}{5x^2-10x+5}:\dfrac{3x+3}{5x-5}\)
\(=\dfrac{x\left(x+1\right)}{5\left(x^2-2x+1\right)}.\dfrac{5\left(x-1\right)}{3\left(x+3\right)}\)
\(=\dfrac{x\left(x+1\right)}{5\left(x-1\right)^2}.\dfrac{5\left(x-1\right)}{3\left(x+1\right)}\)
\(=\dfrac{x\left(x+1\right).5\left(x-1\right)}{5\left(x-1\right)^2.3\left(x+1\right)}\)
\(=\dfrac{x}{3\left(x-1\right)}\)
\(\dfrac{x^2+x}{5x^2-10x+5}:\dfrac{3x+3}{5x-5}=\dfrac{5x\left(x+1\right)\left(x-1\right)}{15\left(x-1\right)^2\left(x+1\right)}=\dfrac{x}{3\left(x-1\right)}\)\(\left(x^2-25\right):\dfrac{2x+10}{3x-7}=\dfrac{\left(x-5\right)\left(x+5\right)\left(3x-7\right)}{2\left(x+5\right)}=\dfrac{\left(x-5\right)\left(3x-7\right)}{2}\)
a ) \(\left(3x^2-4x+5\right)\left(2x^2-4\right)-2x\left(3x^3-4x^2+8\right)\)
\(=\left(3x^2-4x+5\right).2x^2-4\left(3x^2-4x+5\right)-6x^4+8x^3-16x\)
\(=6x^4-8x^3+10x^2-12x^2+16x-20-6x^4+8x^3-16x\)
\(=\left(6x^4-6x^4\right)+\left(8x^3-8x^3\right)-\left(12x^2-10x^2\right)+\left(16x-16x\right)-20\)
\(=-2x^2-20\)
b ) \(\left(1-3x+x^2\right)\left(2-4x\right)+2x\left(2x^2+5\right)\)
\(=2\left(1-3x+x^2\right)-4x\left(1-3x+x^2\right)+4x^3+10x\)
\(=2-6x+2x^2-4x+12x^2-4x^3+4x^3+10x\)
\(=\left(4x^3-4x^3\right)+\left(12x^2+2x^2\right)+\left(10x-6x-4x\right)+2\)
\(=14x^2+2\)
d. ( x2 - 2xy + y2 ) ( x-y )
= ( x- y )2 ( x- y )
= ( x - y )3
b, (x^2+xy+y^2) (x-y)
= ( x+ y )2 ( x- y )
= ( x2 - y 2 ) ( x +y )
a) 2x(3x^2 -5x + 3) = 6x^3 - 10x^2 + 6x
b) -2x(x^2 +5x-3) = -2x^3 - 10x^2 + 6x
c) 2 dấu trừ liền nhau??
bài 2:
a) \(\left(2x-1\right)\left(x^2+1\right)=2x^3-x^2+2x-1\)
b) \(-\left(5x-4\right)\left(2x+3\right)=-\left(10x^2-8x+15x-12\right)=-10x^2-7x+12\)
c) \(\left(2x-y\right)\left(4x^2-2xy+y^2\right)=8x^3-4x^2y-4x^2y+2xy^2+2xy^2-y^3=8x^3-8x^2y+2xy^2-y^3\)
d) \(\left(3x-4\right)\left(x+4\right)+\left(5-x\right)\left(2x^2+3x-1\right)=3x^2+8x-16+10x^2-2x^3+15x-3x^2-5+x=10x^2+24x-21\)
e) \(7x\left(x-4\right)-\left(7x+3\right)\left(2x^2-x+4\right)=7x^2-28x-\left(14x^3+6x^2-7x^2-3x+28x+12\right)=-14x^2+8x^2-53x-12\)
c) (xy-1).(xy+5)
= x2y2+5xy-xy-5
=x2y2+4xy-5
a) b) d) bạn có thể ghi rõ được ko
a.( 5x2-4x).(x-3)=5x3-15x2-4x2+12x=5x3-11x2+12x
b.(2-3xy).(3x4+4y2+5xy)=6x4+8y2+10xy-9x5y-12xy3-15x2y2
c.(-3x2+x+1).(x2+x-5)=-3x4-3x3+15+x3+x2-5x+x2+x-5=-3x4-2x3+2x-4x+10
b: \(B=\dfrac{3y+5}{y-1}-\dfrac{-y^2-4y}{y-1}+\dfrac{y^2+y+7}{y-1}\)
\(=\dfrac{3y+5+y^2+4y+y^2+y+7}{y-1}\)
\(=\dfrac{2y^2+8y+12}{y-1}\)
a: 3x^2y(3x-4y)
=3x^2y*3x-3x^2y*4y
=9x^3y-12x^2y^2
c: (3x+5)(3xy-5x)
=9x^2y-15x^2+15xy-25x